Media Exposure as a Moderator of Environmental Performance, Environmental Management System, and Institutional Ownership on Carbon Emission Disclosure - Fitri Nur Komariyah; Tantina Haryati (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose:. Using media exposure as a moderating influence in publicly traded energy firms in Indonesian Stock Exchange, This study seeks to investigate the impact of environmental performance, environmental management systems, and institutional ownership on carbon emission disclosure Methodology: This research employs a quantitative method, using secondary data from sustainability and yearly reports. The data were combined with moderated regression analysis (MRA) are multiple linear regression. Results: The findings demonstrate that environmental performance and environmental management systems substantially impact carbon emission disclosure, whereas institutional ownership exerts no significant influence. Media exposure amplifies how transparency about carbon emissions is affected by environmental performance, despite its lack of alleviate the impacts of environmental management systems and institutional ownership. Findings: Companies with better environmental performance and environmental management systems tend to disclose carbon emission information more widely. Novelty: This study uses moderating variabel and uses energy sector companies as the research object in examining carbon emission disclosure, which has rarely been investigated in previous studies. Originality: This study offers concrete proof of the connection between environmental factors, governance mechanisms, ownership, and media exposure on carbon emission disclosure.. Conclusion: Environmental performance and management systems promote increased carbon emissions disclosure, however institutional ownership does not affect disclosure practices. Type of Paper : Research Article